2022
DOI: 10.1001/jamanetworkopen.2022.25521
|View full text |Cite
|
Sign up to set email alerts
|

Association of Newborn Telomere Length With Blood Pressure in Childhood

Abstract: Key Points Question Is newborn telomere length (TL) associated with blood pressure in childhood? Findings In this birth cohort study including 485 newborns, participants with a longer birth TL had a significantly lower diastolic and mean arterial pressure at the age of 4 to 6 years. Furthermore, longer newborn TL was significantly associated with lower odds of having high childhood blood pressure. Meaning These results suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…5). In this context we recently demonstrated that telomere length at birth was significantly related to childhood diastolic blood pressure at the age of four [98]. Despite the lack of studies in many fields of age-related health measures, the fact that metabolic outcomes are related to all four cord blood aging biomarkers (Fig.…”
Section: Clinical Relevancementioning
confidence: 95%
“…5). In this context we recently demonstrated that telomere length at birth was significantly related to childhood diastolic blood pressure at the age of four [98]. Despite the lack of studies in many fields of age-related health measures, the fact that metabolic outcomes are related to all four cord blood aging biomarkers (Fig.…”
Section: Clinical Relevancementioning
confidence: 95%
“…In the study of Martens DS et al ( 117 ), the telomere length of newborns has a high predictive value to the telomere length of their later years. In the study of Martens DS et al ( 118 ), it was found that the blood pressure of early school-age children was related to the length of telomere at birth. However, telomere length in childhood is also affected by other factors: Exposure to environmental pollution in early life is closely related to telomere wear ( 104 , 119 ).…”
Section: Discussionmentioning
confidence: 98%
“…Although there are several studies linking PM 2.5 exposure with adverse birth outcomes, the specific mechanisms through which differences in markers of the axis of aging upon PM 2.5 exposure affects health and disease later in life should be further investigated. Nevertheless, recent research has shown that telomere length at birth is associated with lean mass early in life (de Zegher, 2017) and cardiovascular changes in childhood (Kaali, 2021;Martens, 2022).…”
Section: Discussionmentioning
confidence: 99%